PHARMACOKINETIC-PHARMACODYNAMIC CORRELATION FOR MEROPENEM APPLIED TO A BURN CHILD USING A BIOANALYTICAL LIQUID CROMATOGRAPHIC METHOD - Silvia R. C. J. Santos; Cristina Sanches-Giraud; Flávio F. de Souza; David Gómez; Edvaldo Campos; Rodrigo Azevedo; Marcus Ferreira; Jorge Nascimento (Formifarma, LDA., 2011)
Bioanalytical method for LC meropenem quantification in plasma was described. Good absolute recovery (higher than 90%), adequate linearity (0.2-50.0 μg/mL, r2=0.999), high sensitivity (LOQ: 0.2 μg/mL; LOD: 0.1μg/mL) and acceptable stability were shown. Interday/intraday precisions were 2.3%/2.0% and the mean accuracy was 98.9%. Case of one burn patient, 8 yrs, 30 kg, thermal/inhalation injury, 45% TBSA was reported. Meropenem was prescribed to pulmonary infection treatment and dose adjustment was performed by drug plasma monitoring (30th and 44th day of thermal accident), pharmacokinetics and pharmacokinetics-pharmacodinamics (PK-PD) modelling. On 5th and 19th day of meropenem treatment, trough drug plasma concentrations were 0.3 μg mL-1 (2.25 ga day: 0.75 g 8qh, 0.5 hour infusion) and 14 μg mL-1 (3 g a day: 1 g 8qh). Pharmacokinetics was altered on 5th day and also on 19th day, respectively: 1.3 and 3.3 hs (biological half-life); 6.4 and 1.7 mL/min.kg (plasma clearance), 0.7 and 0.5 L/kg (apparent volume of distribution). 40%fT>MIC (percentage of time above the minimum inhibitory concentration) was considered for PK-PD correlation. In conclusion, LC drug plasma monitoring was quite useful to guarantee low risk and drug efficacy. Since the pharmacokinetics is unpredictable in burn patients, the effectiveness of meropenem was reached when dose regimen of 1 g 8qh instead 0.75 g 8qh was applied to the paediatric burn patient.